Extracranial rhabdoid tumours: Results of a SFCE series of patients treated with a dose compression strategy according to European Paediatric Soft tisue sarcoma Study Group recommendations. (January 2022) - Enault, Maxime; Minard-Colin, Véronique; Corradini, Nadège; Leverger, Guy; Thebaud, Estelle; Rome, Angélique; Proust, Stéphanie; Marie-Cardine, Aude; Defachelles, Anne-Sophie; Sarnacki, Sabine; Philippe-Chomette, Pascale; Delattre, Olivier; et al.
Abstract: Background and aims: Extracranial malignant rhabdoid tumours are tumours that mainly affect young children and have a poor prognosis. In 2014, the European Paediatric Soft-tissue sarcoma Study Group developed treatment recommendations consisting in intensive dose chemotherapy every 2 weeks using vincristine-doxorubicin-cyclophosphamide (VDCy) and ifosfamide-etoposide (IE) associated with early surgery and irradiation of tumour sites. Methods: A retrospective study was conducted on children treated in France by these new recommendations up to January 2019. Results: Thirty-five patients were identified. The primary tumour was in miscellaneous soft parts for 18 patients, in the kidney for 11 and in the liver for six. The median age at diagnosis was 17.5 months (range 1.2–198.2). Distant locations (metastatic or synchronous tumours) were present in 37.1% at diagnosis. SMARCB1 germline pathogenic variant was detected in 17.1% of patients. Overall tolerance was good, with 87–97% of theoretical chemotherapy cumulative doses actually delivered. The median interval between two courses was 18 days. Surgical resection was performed in 83% (19 R0, 7 R1 and 3 R2) and local radiotherapy in 49% of patients. After a median follow-up of 50.4 months (range 16.5–134.1), the 2-year overall and event-free survivals were 47.6% (95% confidence interval [CI] 30.2–63.1) and 42.9% (95% [CI] 26.5–58.3), respectively. On univariate analyses, localised disease and gross total resection were significantly associated with favourable outcomes. Conclusions: Intensive dose chemotherapy with VDCy/IE can be administrated with no remarkable short-term toxicity, including in infants. However, the outcome remains poor for patients without gross total resection and with metastatic or multifocal disease. These patients could be stratified into a high-risk group that requires a new immediate therapeutic approach such as targeted agents combined with multimodal therapy. Highlights: Dose-intensity chemotherapy can be safely administered to paediatric patients. Metastatic status and gross total resection are significant prognostic factors. Dose-intense strategy appears at least equivalent to recent studies in treatment of extracranial maligant rhabdoid tumour. Next trials may aim at combining targeted therapies with this backbone.